Music Therapy in Canada: An Interview with Marianne Bargiel - Vaillancourt, Guylaine (Voices: A World Forum for Music Therapy, 2010)
Marianne Bargiel is practicing music therapy since 1991 with children and adults in school, community, and psychiatric facilities. She has taken on Josée Préfontaine’s work at directing the Institut québécois de musicothérapie. She is a candidate for a psychology Ph. D. (Université du Québec à Trois-Rivières) where her main research interest is musically evoked emotional processes in psychopathology.